Islamic Education Marketing Management As a Service Quality Improvement Strategy - Ratnasari Ratnasari (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
The tighter competition in the Islamic Education Sector requires all parties in the Education Sector Business Management to put more effort into optimally and as much as possible in improving the quality of education services in their respective institutions. Islamic Education Marketing Management is a process of planning, organizing, directing, supervising and utilizing resources that are carried out effectively and efficiently in offering Islamic education services. This is a strategy in improving the quality of services and the most important element for the quality and progress of the level of education in an educational institution. Marketing Management is needed (Marketing) right to win the competition. The study method used is descriptive qualitative with the type of library research, and the data presentation method is descriptive analytic.